3D Cartilage Regeneration With Certain Shape and Mechanical Strength Based on Engineered Cartilage Gel and Decalcified Bone Matrix - Ci, Zheng; Zhang, Ying; Wang, Yahui; Wu, Gaoyang; Hou, Mengjie; Zhang, Peiling; Jia, Litao; Bai, Baoshuai; Cao, Yilin; Liu, Yu; Zhou, Guangdong (Frontiers in Cell and Developmental Biology, 2021)
Scaffold-free cartilage-sheet technology can stably regenerate high-quality cartilage tissue in vivo. However, uncontrolled shape maintenance and mechanical strength greatly hinder its clinical translation. Decalcified bone matrix (DBM) has high porosity, a suitable pore structure, and good biocompatibility, as well as controlled shape and mechanical strength. In this study, cartilage sheet was prepared into engineered cartilage gel (ECG) and combined with DBM to explore the feasibility of regenerating 3D cartilage with controlled shape and mechanical strength. The results indicated that ECG cultured in vitro for 3 days (3d) and 15 days (15d) showed good biocompatibility with DBM, and the ECG–DBM constructs successfully regenerated viable 3D cartilage with typical mature cartilage features both in nude mice and autologous goats. Additionally, the regenerated cartilage had comparable mechanical properties to native cartilage and maintained its original shape. To further determine the optimal seeding parameters for ECG, the 3d ECG regenerated using human chondrocytes was diluted in different concentrations (1:3, 1:2, 1:1) for seeding and in vivo implantation. The results showed that the regenerated cartilage in the 1:2 group exhibited better shape maintenance and homogeneity than the other groups. The current study established a novel mode of 3D cartilage regeneration based on the design concept of steel (DBM)-reinforced concrete (ECG) and successfully regenerated homogenous and mature 3D cartilage with controlled shape and mechanical strength, which hopefully provides an ideal cartilage graft for the repair of various cartilage defects.